The Role Of The Bengkulu City Department Of Transportation In The Maintenance Of Street Lights In The Pantai Panjang Area - Pajila Sukmawati; Antonio Imanda; Yanuar Rikardo (Social Sciences Journal, 2026)
This study examines the role of the Bengkulu City Department of Transportation in the maintenance and upkeep of public street lighting in the Pantai Panjang area. Public street lighting plays an essential role in ensuring road safety, comfort, and security for road users, particularly at night. However, various issues such as damaged lights, limited human resources, insufficient budgets, and environmental factors have contributed to suboptimal service quality. Using a qualitative descriptive approach, this research collected data through in-depth interviews, field observations, and documentation. The findings show that the Department of Transportation carries out three main roles based on Soerjono Soekanto’s role theory: the active role, which includes routine monitoring and immediate response to damage; the participatory role, which involves collaboration with communities and relevant agencies such as PLN; and the passive role, in which actions are taken primarily after receiving public complaints due to administrative and resource limitations. The study reveals that despite efforts to maintain and repair street lights, operational constraints, such as limited technical personnel and delays in material procurement, still hinder optimal performance. This research highlights the need for increased budgets, additional technical staff, and strengthened community engagement to enhance the effectiveness of street lighting maintenance. Strengthening these aspects will directly improve public safety, comfort, and the overall quality of public service delivery in the Pantai Panjang area.